ARRDC3 suppresses colorectal cancer progression through destabilizing the oncoprotein YAP. Issue 4 (13th February 2018) - Shen, Xu; Sun, Xiaohan; Sun, Bing; Li, Tao; Wu, Guoliang; Li, Yuantao; Chen, Lai; Liu, Qingxin; Cui, Meng; Zhou, Zizhang
Abstract : Although colorectal cancer (CRC) is a prevalent malignancy of the digestive system, the underlying mechanisms of CRC tumorigenesis are still elusive. Arrestin‐related domain‐containing protein‐3 (ARRDC3) has been reported to promote lysosome‐mediated protein degradation. In the present study, we find that the expression of ARRDC3 is downregulated in CRC specimens. Mechanistically, we reveal that ARRDC3 binds and decreases expression of the oncoprotein YAP, the cotranscription factor of the Hippo pathway. The regulation of the Hippo pathway by ARRDC3 is conserved from Drosophila to mammals. Furthermore, we demonstrate that ARRDC3 plays an anti‐oncogenic role in CRC progression by promoting YAP degradation. Finally, we show that ARRDC3 increases the sensitivity of CRC cells toward chemotherapeutic drugs. Taken together, our findings point to ARRDC3 as a potential target for CRC treatment. Abstract :